COMPLEMENTARY FEEDING AND STUNTING: A LITERATURE REVIEW - Ghita, Dwi (Homes Journal: Hospital Management Studies Journal, 2025)
Approximately 150 million children under the age of five experience stunting. The development of children in the early stages, particularly during the first 1000 days from pregnancy to the age of 2 years, greatly influences an individual’s nutrition and health status throughout their life. Objective: To analyze the provision of complementary feeding to breastfeeding in relation to stunting based on theory, risk factors, screening, and interventions provided. Results: The main factors affecting stunting, such as the provision of complementary feeding to breastfeeding, maternal nutritional status, and the family’s socio-economic conditions, play a significant role in children’s health and development. Conclusion: By optimizing local food resources and involving the community in nutrition programs, it is hoped that sustainable improvements in children’s nutrition and health can be achieved.